A Fluorescent RNA Forced‐Intercalation Probe as a Pan‐Selective Marker for Influenza A Virus Infection. (27th June 2017) - Haralampiev, Ivan; Schade, Matthias; Chamiolo, Jasmine; Jolmes, Fabian; Prisner, Simon; Witkowski, Peter T.; Behrent, Marie; Hövelmann, Felix; Wolff, Thorsten; Seitz, Oliver; Herrmann, Andreas
Abstract: The influenza A virus (IAV) genome is segmented into eight viral ribonucleoproteins, each expressing a negatively oriented viral RNA (vRNA). Along the infection cycle, highly abundant single‐stranded small viral RNAs (svRNA) are transcribed in a segment‐specific manner. The sequences of svRNAs and of the vRNA 5′‐ends are identical and highly conserved among all IAV strains. Here, we demonstrate that these sequences can be used as a target for a pan‐selective sensor of IAV infection. To this end, we used a complementary fluorescent forced‐intercalation RNA (IAV QB‐FIT) probe with a single locked nucleic acid substitution to increase brightness. We demonstrated by fluorescence in situ hybridization (FISH) that this probe is suitable and easy to use to detect infection of different cell types by a broad variety of avian, porcine, and human IAV strains, but not by other influenza virus types. IAV QB‐FIT also provides a useful tool to characterize different infection states of the host cell. Abstract : A good FIT : A pan‐selective influenza A virus (IAV) probe, IAV QB‐FIT, was designed to target the highly conserved IAV vRNA 5′‐ends. This 2′‐O‐methylated RNA oligonucleotide and forced‐intercalation dye‐labeled probe is suitable to specifically detect IAV infections in fixed cells, independent of the cell line used, and can be employed to monitor different infection states.